Artificial intelligence for inclusive and sustainable international education: A critical conceptual review - Duke, Benjamin (Journal of International Students, 2026)
This paper aims to provide a conceptual theoretical review, investigating the role of artificial intelligence and education in advancing international sustainable education. Future global research and international development will benefit by increased understanding of how diversity, equity and inclusion (DEI), alongside international sustainable education, is affected by social and contextual interpretation. The paper provides a critical review of some of the educational methods that can be delivered using AI, which can be adapted to link international development with education. The paper concludes by providing a critical theoretical review of the key issues discussed, regarding the future role of AI will have, in delivering the Sustainable Development Goals (SDGs) in international education whilst enhancing DEI.